ANALISIS FAKTOR EKOLOGI DOMINAN PEMILIHAN KUBANGAN OLEH BADAK JAWA (Rhinoceros sondaicus Desmarest 1822) DI TAMAN NASIONAL UJUNG KULON - Yanto Santosa; Cory Wulan; Agus Hikmat (Department of Forest Resources Conservation and Ecotourism - IPB University, 2010)
The characteristic of wallow can be one of standard or criteria of the javan rhino habitat which will be used for selection strategy of further javan rhino’s wallow. The objective of this study is to identify the wallow characteristic of javan rhino both physical and biological factors that need for identifiying the dominant ecological factor in determining wallow selection strategy for javan rhino. The data that were collected consisted of physical characteristic javan rhino’s wallow i.e. the length and the width of wallow, the depth of mud and water of wallow, water pH inside the wallow, the height of wallow site, the temperature and humidity, and the distance from wallow to the coastal, river, and from human access. The biotic characteristic aspects of javan rhino’ wallow that were observed consisted of the number of javan rhino’ feed and the total density of vegetation spread around the wallow according to result of vegetation analysis. Based on the result of factor analysis, the dominant ecological factor that affect wallow selection are the height of the site (10-87 mdpl), air temperature (26-29°C), and tree density (25-174 ind/ha). Keywords : Javan Rhinoceros, wallow, dominant ecological factor.